Nutritional Content Of Fresh Seed, Pith, Pulp And Red Fruit Paste (Pandanus conoidus lamk) Type Of Mbarugum Origin Papua - Selvia Tharukliling (Universitas Muhammadiyah Sorong, 2022)
Red fruit is an endemic plant of Papua which is rich in bioactive compounds both antioxidants and antimicrobials, the form or fraction of red fruit that is often used is red fruit oil and red fruit paste. Several other red fruit fractions are wasted and have not been utilized because information about their nutritional composition does not yet exist. This study aims to determine the comparison of the nutritional composition of each red fruit fraction starting from fresh seeds, pith, pulp and paste. This study uses laboratory analysis of the proximate value of each fraction, FFA value and carotene value. The results showed that the nutritional value of each red fruit fraction was different, for the value of protein, fat, carbohydrates and crude fiber the highest nutritional value was found in fresh seeds while the lowest value for all compositions except for water content was in the pith fraction. The FFA and carotene values ​​were highest in fresh seeds, then in the pasta and pulp fractions, while FFA and carotene pith were not detected.